Edukasi Peningkatan Kesehatan Tentang Hipertensi Pada Lansia - Suyami Suyami; Puput Risti Kusumaningrum (Universitas Muhammadiyah Klaten, 2024)
Hypertension is a systolic pressure above 140 mmHg and a diastolic pressure above 90 mmHg. Hypertension is called the silent killer because it is one that can be deadly without being accompanied by symptoms first as a warning. The risk of developing hypertension increases with age. Around 2 out of 3 elderly people are estimated to suffer from hypertension. This community service activity aims to provide health improvement education about hypertension in the elderly. The method used in this activity is a pre-post test without a control group. Sampling technique with a total sampling of 10 samples. The instrument used was a knowledge level questionnaire. The results obtained before health education were carried out with poor knowledge were 6 (60%) elderly people, sufficient knowledge was 3 (30%) elderly people, and good knowledge was 1 (10%) elderly person. After being given education, the level of knowledge of the elderly became good knowledge for 7 (70%) elderly people, moderate knowledge for 3 (30%) elderly people. The results after being given education can be seen that the respondents' knowledge has increased and this method is effective in increasing the knowledge of the elderly.